Evaluation of damage in reinforced concrete slabs with different reinforcement ratios using damage indicators and numerical modeling - Ferreira, Gabriel Soares (2019)
Slabs of reinforced concrete (RC) have a different crack pattern in comparison to beams, where the cracks in bending tend to spread on the surface of the element. The reinforcement ratio is also a factor that can change this pattern. In order to evaluate the effect of damage on cracking pattern, natural frequency and mode shapes in RC slabs, two of such structures with different dimensions and reinforcement ratios in both directions were tested, in which cracks were induced through application of static load, followed by modal tests using impact excitation. Extracting the frequencies and mode shapes using StarModal software, different damage indexes were used to compare both slabs, bearing in mind that differences in the cracking pattern occurred in both structures. To understand the reason for a different behavior, both slabs were modelled numerically using finite elements. The model considering the loss of stiffness in the finite element which have the crack and its nearby elements showed better results than the model in which the stiffness reduction was applied in all elements that reached the cracking moment; the comparison was made through the evaluation of frequencies and modal parameter MAC, which indicate that the cracking affects locally the stiffness of the elements. Isotropic and orthotropic models did not show significant diferences among themselves, what brings inconclusive results about the transition from isotropic to orthotropic behavior as the cause of different cracking pattern. The slopes in loading and unloading stages presented values relatively close to each other, indicating that the models, although adjusted for unloading stage, can also be used for the loading stage.